2008
DOI: 10.2174/1876822900901010001
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tumor Volume on Outcomes after Radical Prostatectomy: Implications for Prostate Cancer Screening

Abstract: Abstract:Purpose: For screening to make an impact on prostate cancer mortality, detection of potentially lethal cancers at an early stage when they are low volume should result in improved recurrence and death rates after treatment. Patients and Methods:The effect of tumor volume on prostate cancer recurrence and death was evaluated in 764 men who underwent radical prostatectomy between 1984 and 2004, with particular attention focused on patients with moderate and high risk features. Results: Tumor volume was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 14 publications
(24 reference statements)
1
17
0
Order By: Relevance
“…Surgeries were performed between 1998 and 2007, and detailed clinical data, including follow-up and recurrence status, were available in 96 patients (88%). Mean patient age, pre-operative serum PSA levels, clinical stage, and pathological Gleason grade were compatible with the risk profiles of contemporary patients undergoing surgery for prostate cancer (Supplemental Table S1; Brooks et al 2008).…”
Section: Resultssupporting
confidence: 53%
“…Surgeries were performed between 1998 and 2007, and detailed clinical data, including follow-up and recurrence status, were available in 96 patients (88%). Mean patient age, pre-operative serum PSA levels, clinical stage, and pathological Gleason grade were compatible with the risk profiles of contemporary patients undergoing surgery for prostate cancer (Supplemental Table S1; Brooks et al 2008).…”
Section: Resultssupporting
confidence: 53%
“…The median followā€up time for our patient population was insufficient to detect whether PSM length was associated with prostateā€cancerā€specific survival. In a larger cohort of patients, we have previously reported that the presence of positive surgical margins is associated with biochemical recurrence and cancerā€specific survival 8 . Unfortunately, data regarding the length and location of positive margins was not available for all patients in that cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Between 1984 and 2004, 789 patients underwent radical prostatectomy with standard pelvic lymph node dissection at the Stanford University Hospital and Clinics and signed informed consent for collection of their clinical and pathological data. The clinical and pathological features of the entire cohort are summarized elsewhere 8 . In total, 140 of these men who underwent radical prostatectomy for clinically localized prostate cancer were identified as having PSM.…”
Section: Methodsmentioning
confidence: 99%
“…Many of these localized PCas are treated by surgical removal of the entire prostate (radical prostatectomy). The presence of cancer cells at the edge of the surgical resection, or positive surgical margins, is associated with higher rates of recurrence and death from PCa (3,4). Therefore, an important clinical challenge in PCa management is to devise a rapid and highly accurate method to detect cancerous cells in real time to allow resection of additional periprostatic tissues and reduce cancer recurrence after surgery.…”
mentioning
confidence: 99%